Correlation Between Serum Ferritin And Liver Function in Thalassemia Patients - Zainab Qasim Muhammad Al-Yasiri (Indian Journal of Forensic Medicine & Toxicology, 2021)
Thalassemia ,is one of the most important hemolytic genetic, diseases that break down red blood cells,Children with thalassemia cannot produce. enough hemoglobin because; the bone marrow cannot produceenough red blood cells to meet their needs and the red blood cells produced ,by them are almost devoid ofhemoglobin, and the disease is divided into alpha, and Beta thalassemia.The current study was designed with the aim of .investigating the relationship between serum ferritin andhepatic enzymes in thalassemia. patients, iron is stored primarily in the form of ,ferritin in liver cells. Thestudy included 60 patients with thalassemia in; Dhi Qar governorate, distributed between. the two genderduring the, research period, their ages ranged between (2 -26) years old, blood samples were taken in orderto testing of. hemoglobin, ferritin, and liver enzymes (ATP, GOT, GPT) , and the same, tests were performedon healthy people 40 person ;as they are a control group.The results recorded; a high percentage of ,thalassemia incidence in males and a decrease in females. Thestudy also showed; that the incidence of thalassemia reached its peak in the age. group (2-6) years anddecreased with age, as it reached its lowest levels in the age, group (22-26) years.The study revealed .a significant decrease (0.05> P) in hemoglobin concentration in thalassemia, patientscompared with the ;control group, and the results recorded a significant; increase (0.05 P <) in theconcentration of ferritin in thalassemia, patients compared with the control group.The current study; also showed a significant increase (P <0.05) in GPT enzyme concentration in thalassemia.patients compared with the control group. There was a significant increase (P <0.05) of GOT enzyme;concentration in patients compared to the ,control group.The results indicated. that there was a significant increase (P <0.05) in the concentration of the ALP enzymein the patients. compared with the control group.